2021
DOI: 10.3389/fcvm.2021.754499
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril-Valsartan, Clinical Benefits and Related Mechanisms of Action in Heart Failure With Reduced Ejection Fraction. A Review

Abstract: Heart failure (HF) is a clinical syndrome characterized by the presence of dyspnea or limited exertion due to impaired cardiac ventricular filling and/or blood ejection. Because of its high prevalence, it is a major health and economic burden worldwide. Several mechanisms are involved in the pathophysiology of HF. First, the renin-angiotensin-aldosterone system (RAAS) is over-activated, causing vasoconstriction, hypertension, elevated aldosterone levels and sympathetic tone, and eventually cardiac remodeling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 110 publications
0
26
0
Order By: Relevance
“…Also, ARNI has recently received attention as an effective basic HF drug and is recommended prior to ACEi/ARB in patients with HFrEF if applicable according to current guidelines ( 7 10 ). ARNIs are effective for LV and LA reverse remodeling ( 36 39 ). Moreover, ARNIs are reported to reduce the SMR ( 40 ).…”
Section: Pharmacological Treatment For Dynamic Smrmentioning
confidence: 99%
“…Also, ARNI has recently received attention as an effective basic HF drug and is recommended prior to ACEi/ARB in patients with HFrEF if applicable according to current guidelines ( 7 10 ). ARNIs are effective for LV and LA reverse remodeling ( 36 39 ). Moreover, ARNIs are reported to reduce the SMR ( 40 ).…”
Section: Pharmacological Treatment For Dynamic Smrmentioning
confidence: 99%
“…In terms of reducing the incidence of cardiovascular diseases, studies have shown that enkephalinase inhibitors can not only reduce myocardial fibrosis and improve cardiac remodeling, but also increase the antiarrhythmic effects of enkephalin, endorphin and bradykinin [49], reduce the incidence of cardiovascular disease and thus prevent the occurrence of cognitive impairment. In addition, chronic hyperglycemia is also a crucial risk factor for cognitive impairment [50], and sacubitril-valsartan can improve glycemic control [51], so the use of ARNI can reduce cognitive impairment in hypertensive patients with diabetes, which has considerable guiding significance.…”
Section: Protection Of Cognitive Function By Sacubitril-valsartanmentioning
confidence: 99%
“…Moreover, omapatrilat, the first dual inhibitor of both neprilysin and ACE, produced a higher incidence of potentially life-threatening angioedema than enalapril, despite its greater efficacy in reducing blood pressure. Hence, further development of omapatrilat as an antihypertensive was terminated ( Greenberg 2020 ; Pascual-Figal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%